Marshall P. Wilder and Disability Performance History - Susan Schweik (Disability Studies Quarterly, 2010)
Marshall P. Wilder, born in 1859, was a highly visible public figure who is now forgotten. A famous vaudeville performer often described as a “hunchback dwarf,” Wilder played dynamically with the disabling discourses that framed him, and he resisted tokenization by developing and claiming cross-disability (as well as cross-class) alliances with marginalized others. His work speaks not only to disability studies but to the conjunction of performance studies and critical prison studies. Early in the last century, he set the stage for productive connections to be made in this one between the theaters of disability, poverty and incarceration.